ORAL CLONIDINE FOR ATTENUATION OF HAEMODYNAMIC RESPONSE TO LARYNGOSCOPY AND ENDOTRACHEAL INTUBATION IN KNOWN HYPERTENSIVE PATIENTS - Islam, Mujahid -ul-; Ahmad, Imtiaz; Rafique, Khalid; Kamal, Rehana; Abbas, Faahad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Sympathetic response associated with laryngoscopy and endotracheal intubation is recognised as a potential cause for a number of complications especially in hypertensive patients. Various methods have been used to attenuate these haemodynamic responses; however most of the studies are in normotensive patients. The aim of our study was to compare the effect of oral clonidine and I/V fentanyl with oral placebo and I/V fentanyl in attenuating the haemodynamic responses to laryngoscopy and intubation in known hypertensive patients. Method: In a double blind randomised controlled trial, 60 hypertensive patients, taking antihypertensive drugs and with systolic blood pressure below 160 mmHg and diastolic blood pressure below 100 mmHg scheduled for elective surgeries, requiring oral endotracheal intubation and age ranging from 40-65 years were included in this study and randomly divided into Group A (clonidine 0.2 mg + fentanyl 2 Î¼g/Kg) and Group B (Placebo + fentanyl 2 Î¼g/Kg). Results: Demographic data were comparable in both groups. There were no statistically significant differences between the two groups in the duration of laryngoscopy and intubation. There was statistically significant attenuation in heart rate in both groups (p=0.020). The trends of attenuation of systolic blood pressure, diastolic blood pressure and mean arterial pressure in Group A compared to Group B, were statistically significant (p=0.034, 0.011, 0.011 respectively). Conclusion: Clonidine, under the present study design attenuates the haemodynamic response to laryngoscopy and endotracheal intubation in known hypertensive patients. Keywords: Clonidine, haemodynamic response, laryngoscopy, endotracheal intubation, hypertension